Comparison of Periodic Flow Fields in a Radial Pump among CFD, PIV, and LDV Results - Jianjun Feng; F.-K. Benra; H. J. Dohmen (International Journal of Rotating Machinery)
The interaction between the impeller and the diffuser is considered to have a strong influence on the unsteady flow in radial pumps. In this paper, the unsteady flow in a low specific speed radial diffuser pump has been simulated by the CFD code CFX-10. Both Particle Image Velocimetry (PIV) and Laser Doppler Velocimetry (LDV) measurements have been conducted to validate the CFD results. Both the phase-averaged velocity fields and the turbulence fields obtained from different methods are presented and compared, in order to enhance the understanding of the unsteady flow caused by the relative motion between the rotating impeller and the stationary diffuser. The comparison of the results shows that PIV and LDV give nearly the same phase-averaged velocity fields, but LDV predicts the turbulence much clearer and better than PIV. CFD underestimates the turbulence level in the whole region compared with PIV and LDV but gives the same trend.